Predictive value of microRNA-133a-3p for early urinary incontinence after radical prostatectomy for prostate cancer and its correlation with rehabilitation effects - Fan Yang; Qiuxia Qin; Juan Liu (Hereditas)
Abstract Aim The present study was conducted with the objective ascertaining the clinical implication of microRNA-133a-3p (miR-133a-3p) for urinary incontinence (UI) and rehabilitation effects in prostate cancer after radical prostatectomy. Methods The measurements of miR-133a-3p in urethral tissue samples from prostate cancer patients after radical prostatectomy were carried out via quantitative real-time polymerase chain reaction (qRT-PCR) detection. Receiver operation characteristic (ROC) curve and logistic regression analysis were employed for evaluating the predictive significance of miR-133a-3p for the early UI of prostate cancer patients with radical prostatectomy. Bioinformatics tools were employed for mining the miR-133a-3p possible genes. Results An obvious reduction of miR-133a-3p was detected in patients with UI compared with those with urinary continence (UC) (P < 0.001), demonstrating a high diagnostic capacity for patients with UI. Moreover, miR-133a-3p could be an independent predictive index for the early UI in patients with prostate cancer after radical prostatectomy (P < 0.001). Additionally, urine miR-133a-3p was notably increased in the UI patients after rehabilitation (P < 0.001). MiR-133a-3p largely concentered on the muscle-related diseases pathways using bioinformatics tools. Conclusion MiR-133a-3p was a promising indicator for predicting early UI in patients with prostate cancer after radical prostatectomy. Clinical trial number Not applicable.